Means of displaying the spring-summer cycle of Ukrainian calendar rites in folk stage dances by ballet masters - Volchukova, Viktoriia; Tishchenko, Olena (Professional Art Education, 2024)
The article the effective means of displaying the spring-summer cycle of Ukrainian calendar rites in folk dance ensembles by choreographers have been identified and theoretically substantiated, namely: dance vocabulary of Ukrainian folk stage dance, dramaturgy of the work, dance patterns, Ukrainian folk costumes, the Kupala tree, Ukrainian folk and mythological images: Ivan Kupala, Marena, lyrical images of Ukrainian girls, courageous images of Ukrainian boys, images of birds, Spring. The features of vesnyanka, haivka and Kupala rites of Ukrainians and the specifics of their display by Ukrainian choreographers in modern choreographic works have been highlighted.Methods and methodology. The following theoretical methods were used in the study: the method of analysis and synthesis was used for the purpose of researching literary sources on the subject of a scientific article; the method of systematization of information sources made it possible to systematize different views of scientists on the problem being studied; the method of terminological analysis was used to clarify and specify the content of the concepts: «freckles», calendar rites of Ukrainians»; the culturological method was used to analyze the peculiarities of the display of Ukrainian calendar rites by ballet masters in folk stage dances; activity approach - was used to analyze the ritual dances of modern  Ukrainian ballet masters and the specifics of their use of expressive means of dance in them.The scientific novelty lies in the fact that for the first time effective means of displaying the spring-summer cycle of Ukrainian calendar rites by ballet masters in folk dance ensembles have been discovered, namely: dance vocabulary of Ukrainian folk stage and stylized dance, dramaturgy works, dance drawings, Ukrainian folk, Ukrainian folk and mythological images: Ivan Kupala, Marena, lyrical images of Ukrainian girls, courageous images of Ukrainian boys, images of birds, Spring; the essence of the key concepts of the study was specified and concretized: «calendar rites of Ukrainians», «freckles».Results. As a result of the scientific research, it was found that the calendar rituals of the springsummer cycle are associated with certain natural phenomena or the change of seasons, for example, the ritual of Ivan Kupala or the spring equinox ritual, during which vesnianky were performed. Additionally, the classification of vesnianky has been refined: zaklykalni (invocative) – invoking the arrival of spring (the Volyn-Podlasie “rogulky”); khorovodni (round-dance songs) (greeting and praising the arrival of spring); haivky (related to Easter celebrations by the time of their performance); Yuriyivski, Tsarski, and Rusalni (Trinity and bush rituals). An analysis was conducted on the repertoire of amateur and professional folk dance ensembles in Ukraine that reflect the rituals of spring welcoming and Kupala rituals, namely: the Honored Academic Bukovinian Song and Dance Ensemble, whose repertoire includes the one-act ballet by H. Asenkova; the Honored Dance Ensemble of Ukraine «Yunost» with the choreographic ethno-performance «Look at Our Land,» which showcases the ritual of Ivan Kupala (choreographer M. Vankovska); the People’s Dance Ensemble «Barvinok» with the choreographic piece «Ivan Kupala» (choreographer M. Kvitchata), and the choreographic group «Kraski Tantsa» with the production «Kupala Festivities» (choreographer S.Zhitskaya).Conclusions. Thus, a distinctive feature of Ukrainian ritual dances of the spring-summer period is the organic combination of words, music, mimics, dance vocabulary (mainly round dances), dramaturgy (syncretism), Kupala and spring artistic images (Spring, birds, Ivan Kupala, young girls and boys), compositional patterns, national attributes (wreaths, Kupala tree, river, fire), and Ukrainian national costumes (embroidered shirts, tunics, ribbons, wreaths), which ensure the integrity of the phenomenon. Considering the expressive means of dance (music, compositional patterns, dance vocabulary, artistic images, dramaturgy), Ukrainian ritual dances of the spring-summer cycle are divided into the following groups:1. Dances with a circular structure featuring one, two, or a group of girls around (Marena, Kupala);2. Single-line dances («Kryvyi Tanets»);3. Double-line dances («Verbova Doshechka»). It should be noted that the theoretical propositions of the article can be used by choreography teachers, leaders of dance groups, and ballet masters in the creation of highly artistic choreographic works based on Ukrainian calendar rituals.
Keywords: Ukrainian calendar rituals; ballet master; folk-stage dances; expressive means of dance; folk dance ensembles; spring-summer cycle of rituals